Dragon's gate - Yep, Laurence (HarperCollins, 1993)
When he accidentally kills a Manchu, a fifteen-year-old Chinese boy is sent to America to join his father, an uncle, and other Chinese working to build a tunnel for the transcontinental railroad through the Sierra Nevada mountains in 1867.